فاعلية برنامج مقترح للرفع من مستوى المساندة بين الزوجين للتكفل بطفل في وضعية إعاقة - أنفال نوري; بوخزنة وهيبة (جامعة الوادي - University of Eloued, 2025)
"ملخص الدراسة: سعت هذه الدراسة إلى بناء برنامج إرشادي نفسي يهدف إلى رفع مستوى المساندة بين الزوجين المتكفلين بطفل في وضعية إعاقة، انطلاقًا من ملاحظة ميدانية قامت بها الباحثتان لحالات عديدة واردة إلى عيادة “إسراء الخير للصحة النفسية والأرطوفونية”، حيث تبين وجود صعوبات نفسية واجتماعية تؤثر سلبًا على العلاقة الزوجية وتحد من قدرة الأزواج على التفاهم والتكافل في ظل ضغوط الإعاقة. ومن أجل تشخيص الوضع بدقة، قامت الباحثتان بإجراء دراسة استطلاعية على عينة مكونة من ثلاثين زوجًا (أي ستين فردًا)، وتم بناء مقياس خاص لقياس مستوى المساندة النفسية بين الزوجين، اشتمل على أربعة أبعاد: المساندة العاطفية، المساندة العملية، المساندة الاجتماعية، والمساندة في مواجهة الضغوط. كشفت النتائج عن تدنٍ واضح في بعض أبعاد المساندة، لا سيما العاطفية ومواجهة الضغوط، مما أبرز ضرورة التدخل من خلال برنامج إرشادي متخصص. بناء على تلك المعطيات، قامت الباحثتان بتصميم برنامج إرشادي نفسي موجه، تم تطبيقه على عينة تجريبية مكونة من أربعة أزواج تم اختيارهم عشوائيًا من بين ذوي الدرجات الضعيفة في المقياس. امتد البرنامج لمدة شهر ونصف، بمعدل ثلاث حصص أسبوعيًا، وضم مجموعة من الجلسات التفاعلية والأنشطة الإرشادية التي تهدف إلى تحسين التفاهم والتواصل، تقاسم الأدوار الأسرية، تنشيط العلاقات الاجتماعية، وتدريب الأزواج على استراتيجيات فعالة في مواجهة الضغوط المرتبطة بوضعية الإعاقة. وقد أظهرت نتائج القياس البعدي تحسنًا ملحوظًا في جميع أبعاد المساندة النفسية، كما بينت الاختبارات الإحصائية وجود فروق دالة إحصائيًا بين نتائج القياس القبلي والبعدي لصالح البعدي، مما يؤكد فاعلية البرنامج، كما دعمت المقابلات والملاحظات الميدانية هذا التحسن، حيث لوحظ تغيير إيجابي في سلوك وتفاعل الأزواج. خلصت الباحثتان إلى أن التدخل الإرشادي النفسي، إذا ما تم بناؤه على معطيات واقعية وأسس علمية، قادر على تحسين العلاقة الزوجية بشكل فعّال، خاصة لدى الأزواج الذين يعانون من ضغوط إضافية مرتبطة بتكفلهم بأطفال من ذوي الاحتياجات الخاصة. وعليه، أوصت الدراسة بتعميم مثل هذه البرامج الإرشادية في العيادات النفسية والمراكز التربوية، وأكدت على أهمية دمج الأبعاد النفسية والاجتماعية في التكفل الأسري المتكامل." ":study title A Proposed Counseling Program to Enhance Spousal Support in Caring for a Child with a Disability This study aimed to design a psychological counseling program to enhance the level of spousal support between couples caring for a child with a disability. The researchers were motivated by their field observations of numerous families attending ""Israa Al-Kheir Psychological and Orthophonic Clinic،"" where they noted psychological and social difficulties negatively affecting marital relationships، particularly under the pressures associated with the child’s condition. To accurately assess this issue، the researchers conducted an exploratory study involving a sample of 30 couples (60 individuals). They developed a specific scale to measure spousal support، which included four dimensions: emotional support، practical support، social support، and support in coping with stress. The results revealed low levels of support in certain areas، especially emotional support and stress management، highlighting the need for a targeted counseling intervention. Accordingly، the researchers designed a specialized counseling program and applied it to an experimental sample of four couples who had shown low scores on the support scale. The program lasted one and a half months، with three sessions per week. It consisted of interactive guidance sessions and activities aimed at improving communication، sharing family responsibilities، strengthening social ties، and equipping couples with strategies to cope with the psychological pressures associated with disability. Post-intervention results showed a significant improvement in all support dimensions. Statistical analysis confirmed the presence of meaningful differences between pre- and post- program results in favor of the post-test scores، indicating the program’s effectiveness. Observations and semi-structured interviews further supported these findings، revealing noticeable positive changes in the couples' interactions and behaviors. The researchers concluded that when counseling interventions are built upon real-life observations and scientific principles، they can effectively enhance marital relationships، particularly in families facing the added burden of caring for a child with special needs. The study recommended the wider implementation of such programs in psychological and educational centers and emphasized the importance of integrating psychological and social dimensions in comprehensive family support."
مذكرة ماستر قسم علم النفس وعلوم التربية تخصص تربية خاصة
Keywords: البرنامج; المساندة; الزوجين; التكفل بالطفل; الإعاقة; Program; support; couples; childcare; disability